Combined effect of nano boron,zinc, bio-inoculum and white fungus waste on P. aeruginosa numbers and amidase activity in soil. - Zahraa J. Al-Budairy; Luma S. Al-Taweel (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
An experiment was conducted at an agricultural site affiliated with the Department of Agricultural Research at the Diwaniyah Research Station in Iraq on January 15,2024. The aim was to investigate the effects of three study factors, the first factor, a biofertilizer represented by P. aeruginosa bacteria, symbolized as B, applied at two levels (no addition  of P. aeruginosa B0, addition P. aeruginosa B1),  the second factor, white mushroom waste, symbolized as Ab, added at three levels, (no addition of Ab0, 5 tons h-1 as a second level Ab1, 10 tons h-1 as a third level Ab2), and the third factor, a nanofertilizer symbolized as N, applied at four levels, (no addition N0, 4 kg h-1 nanozinc N1, 2 kg h-1 nanoboron N2, and 1 kg h-1 nanoboron + 2 kg h-1 nanozinc N3). These factors were tested for their effects on the number of the bacteria P. aeruginosa and stimulation of amidase enzyme activity in the first harvest of stevia crop.  The statistically analyzed data indicated that the synergistic effect between the three study factors showed significant superiority through increasing the number of P. aeruginosa bacteria and the activity of the amidase enzyme during the two periods, Considering that for the two periods in view, it recorded (153.7,137.7) ×107  CFU g-1 dry soil and (265.33, 163.00) µg N-NH4+ g-1 soil 2h-1, respectively, while the control  treatment recorded the lowest values during two periods, with (44.3,24.7) CFU g-1 dry soil and (61.33,21.67) µg N-NH4+g-1 soil 2h-1, respectively.